2009
DOI: 10.1007/s12541-009-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roll patterns on the Ink transfer in R2R printing process

Abstract: Ink transfer process from the printing roller to the web was investigated using a CFD technique for the roll-to-roll printing applications. A parametric study was conducted to identify the effects of roll pattern geometry on the ink transfer process. In order to make the present analysis more relevant to the real printing system, 3-D computational configuration was set up using the information obtained from the typical roll-to-roll system. Simplified one-dimensional semi-analytic analysis based on Reynolds equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Since the present configuration involves a continuous distortion of free surface formed by the ink, the popular VOF method 15 incorporated in the Fluent Package which uses CSF (continuum surface force) model was invoked to track the interface between the ink and the environmental air and subsequently to obtain a volume fraction C as was done in Lee & Na. 14 The density and the viscosity of the working fluid are matched to those of the silver ink (Parelec Inc.) being used in the printed electronics industry as described in Table 2. Values for surface tension and contact angle were measured at the given viscosity of 0.3 Pa-s.…”
Section: Fluid Analysismentioning
confidence: 99%
“…Since the present configuration involves a continuous distortion of free surface formed by the ink, the popular VOF method 15 incorporated in the Fluent Package which uses CSF (continuum surface force) model was invoked to track the interface between the ink and the environmental air and subsequently to obtain a volume fraction C as was done in Lee & Na. 14 The density and the viscosity of the working fluid are matched to those of the silver ink (Parelec Inc.) being used in the printed electronics industry as described in Table 2. Values for surface tension and contact angle were measured at the given viscosity of 0.3 Pa-s.…”
Section: Fluid Analysismentioning
confidence: 99%
“…However, a recent study 20 reported that the time for the combined drying and curing processes could be successfully reduced by a factor of as large as 5. Therefore, higher web, handling speeds of up to 30 mpm (¼0.5 m/s) compared to the speeds chosen in previous studies, [17][18][19] was considered in this study. Obviously, a relatively higher speed shortens the convection time-scale, thus increasing the importance of the inertial effect relative to that of viscous action.…”
Section: Numerical Configuration and Parametersmentioning
confidence: 99%
“…For the purpose of development and proper validation of the numerical methodology at the first stage, this study aims to establish the effects of the various roll patterns shown in Figure 2 in terms of the shape of the transferred ink, which is a very important task for improving the printing quality. 17 Considering recent progress in reducing the time required for curing and drying processes, 20 the web handling speed used in earlier studies [17][18][19] was raised by a factor of up to 5 in this study. This significant increase in the web moving speed is expected to deteriorate the printing quality due to the enhanced effect of convection.…”
Section: Non-newtonian Fluid Representing the Shear-thinning Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee and Na (2009) and Kim et al (2012) studied the ef-fects of roll pattern geometry on ink transfer process in R2R. Lee and Na (2009) and Kim et al (2012) studied the ef-fects of roll pattern geometry on ink transfer process in R2R.…”
Section: Introductionmentioning
confidence: 99%